TRANSLATION TECHNIQUES AND QUALITY IN THE ENGLISH VERSION OF NGANTING MANUK TEXT - Muhizar Muchtar; Farida Repelita Waty Kembaren (State Islamic University of North Sumatra Indonesia, 2018)
The aims of this study are to identify translation techniques in the English version of nganting manuk text, to elaborate reasons of applying the most dominant translation technique in the English version of nganting manuk text, and to describe the translation quality of nganting manuk text in accuracy, acceptability, and readability aspects. This descriptive qualitative research is an embedded-case study and oriented to translation product. The data consist of words, phrases, clauses, and sentences in nganting manuk text, and the translation quality information from the key informants. The data are collected by document analysis, questionnaire, and analyzed by interactive data analysis technique. There are 10 translation techniques to translate nganting manuk text; borrowing, amplification, adaptation, literal, reduction, established equivalent, transposition, modulation, discursive creation, generalization, and the most dominant technique is borrowing influenced by the translator’s foreignization perspective. The translation quality is good enough; accuracy (70.4%), acceptability (63.4%), and readability (66.1%). One proposed theory is to use Cultural Information Philosophy (CPI) in the footnote to get the reader understanding the local wisdom of Karonese and the philosophy of nganting manuk text. Keywords: nganting manuk, translation technique, quality.